Accessibility to Health-Information and Family Influence on Reproductive Health Literacy Amongst Adolescent Girls - Joseph, Fasoranti Afolabi; Onwuama, Mercy; Toluwalase, Aladesokun (Journal of Physical Education Health and Sport, 2018)
Opportunities for young girls in sexual health education is being discriminated against because there are beliefs that girls that know too much can become wayward. Adolescent girls are faced with so many challenges ranging from cultural and parental pressures. This study sought to evaluate the access to health information and family influence on reproductive health literacy amongst adolescent girls. The sample size comprised two hundred and fifty females (n-250) students selected through purposive sampling method. The research instrument is a self-developed structured and validated questionnaire while descriptive statistics of frequency counts and percentages was used to analyze the responses. Two hypotheses were postulated. Findings showed that access to health information regarding reproductive health is limited and also family influence reproductive health literacy. The study therefore recommends that parents should educate their young daughters about family planning method and teachers should take out time from their allotted schedule to discuss sexual related issues with the adolescents in the school.